Jovian atmospheric studies with the Galileo near infrared mapping spectrometer: An update - Irwin, P; Taylor, F; Carlson, R; Baines, K; Weir, A; Cameron-Smith, P; Calcutt, S; Encrenaz, T; Drossart, P; Roos-Serote, M; Lellouch, E (1999)
In its first two years of operation since arrival at Jupiter in December 1995, the Near Infrared Mapping spectrometer (NIMS) on the Galileo orbiter spacecraft obtained extensive coverage of the planet, including detailed coverage of the north equatorial belt (NEB) 'hot spot' region and the Great Red Spot. We will present the current state of data analysis including recent results on the abundances and variability of several minor constituents (H2O, CH4, NH3, GeH4, CH3D and PH3) and the cloud structure and morphology. (C) 1999 COSPAR. Published by Elsevier Science Ltd.